The Impact of Organizational Culture and Work Discipline on Work Productivity: The Mediating Role of Work Motivation in Expeditionary Companies in Indonesia - Hakim, Lukman; Sabil, Sabil; Lestiningsih, Amin Setio; Puji Widodo, Dwiyatmoko; Sofyanty, Devy (Dinasti Publisher, 2024)
Abstract: This study aims to analyze the mediating role of work motivation on the relationship between organizational culture, work discipline, and work productivity in expedition service companies in Indonesia. Data were collected from 150 respondents who were randomly selected employees of expedition companies. The research method used is quantitative with Structural Equation Modeling - Partial Least Square analysis tool. The results showed that: Organizational culture has a positive but insignificant effect on work motivation (P-Value = 0.104 > 0.05).Organizational culture has a positive but insignificant effect on work productivity (P-Value = 0.429 > 0.05). Work discipline has a negative and significant effect on work motivation (P-Value = 0.003 < 0.05). Work discipline has a positive and significant effect on work productivity (P-Value = 0.000 < 0.05). Work motivation has a positive but insignificant effect on work productivity (P-Value = 0.182 > 0.05). The mediation test results show that: Work motivation does not mediate the effect of organizational culture on work productivity (P-Value = 0.360 > 0.05). Work motivation does not mediate the effect of work discipline on work productivity (P-Value = 0.253 > 0.05). Keywords: Work Productivity, Work Motivation, Work Culture, Work Discipline